FAKTOR-FAKTOR YANG MEMPENGARUHI PENYAKIT ISPA PADA BALITA DI WILAYAH KERJA PUSKESMAS SIMBUR NAIKTAHUN 2023 - Suriani (Nightingale: Journal of Nursing, 2024)
Acute Respiratory Infection (ARI) is an environmental-based disease that spreads through the air. This disease can be transmitted if the virus or bacteria contained in the droplets is inhaled by a healthy person. Infected droplets can be spread by coughing or sneezing. The aim of this research is to find out how these factors influence ARI in toddlers in the Simbur Naik Community Health Center working area. The design used in this research is correlational analytics with a cross sectional approach. The population in this study were mothers of toddlers who had a history of suffering from ISPA in the Simbur Naik Community Health Center working area, Muara Sabak Timur District, East Tanjung Jabung Regency. In this research, the sampling technique used was total sampling. Data were collected using a questionnaire using the Chi Square statistical test with SPSS 25 software where p<0.05. The results of the study showed that 40 respondents were known to have ARI incidents in the work area of the Simbur Naik Community Health Center, Muara Sabak Timur District, East Tanjung Regency, showing Age < 2 years (70%), Incomplete Immunization Status (72.5%), Poor Knowledge (72.5%) and unhealthy residential density (50%) with the incidence of ISPA in the Simbur Naik Community Health Center area. The results of the Chi Square Test showed that the influence of toddler age on the incidence of ISPA was p-value = 0.04, mother's knowledge on the incidence of ISPA was p-value = 0.01, immunization status was on the incidence of ISPA p-value = 0.01 and room occupancy density was incidence of ARI p-value = 0.01. This result shows that the direction of the correlation is positive with a significant influence. So H0 is rejected and H1 is accepted. The conclusion is that there is a significant and influential relationship between the factors that influence acute respiratory infections in toddlers in the Simbur Naik Community Health Center working area.